ANALISIS INVESTASI ASING LANGSUNG DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYADI INDONESIA: ANALISIS INVESTASI ASING LANGSUNG DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYADI INDONESIA - Astuty, Fuji (UNIVERSITAS SARI MUTIARA INDONESIA, 2017)
Foreign Direct Investment gave benefits in improving Indonesia's economics matters in Indonesia. Conseptually, Foreign Direct Investment (FDI) more benefecial because no return to the investor such as debt in foreign country, beside Foreign Direct Investment (FDI) in a country will be followed by transfer of technology, know-how, management skills, the risks of business was smaller and more profitable. However, the problem of global economic that occured affecting the development of Foreign Direct Investment (FDI) in Indonesia decreased and the growth became slowly. Then domestic and global factors weren’t stable influencing the decrease Foreign Direct Investment (FDI) in Indonesia. Therefore, it’s needed to examine the factors influencing Foreign Direct Investment (FDI). This study aimed to know and analyze some factors affecting Foreign Direct Investment (FDI) in Indonesia consisting gross domestic product, the level of real interest, exchange rates, labour produtivity, and exports. The affecting analysis be done in short-time by using Error Correction Mechanism = ECM technique. It was used time series data from 2000 to 2013 using Eviews 6.0. The type of data used was secondary data obtained from Indonesia Bank (BI), Central Bureau of Statistics (BPS), Federal Reserve Bank of St. Louis and United Nations Economic Social Commision for Asia and the Pacific (UNESCAP). The results of this study showed that gross domestic product, the level of real interest, exchange rates, and labour productivity had positive affection significantly on Foreign Direct Investment (FDI) in Indonesia. While the exports had negative affection significantly on Foreign Direct Investment (FDI) in Indonesia. From determination coefficient (R2) showed that the variables explained 97.13 percent on Foreign Direct Investment (FDI) in Indonesia while the rest 2.87 percent was explained by variables out of models (not studied).Keywords : Foreign Direct Investment, Gross Domestic Product, the level of Real Interest, Exchange Rates, Labour Produtivity, and Exports.